Preparation of Silica Gel G Loaded Nano-barium Titanate and Its Adsorption Capability to Zinc in Water - Zhang, Dong; Cheng, Yan (Asian Journal of Chemistry, 2013)
The silica gel G loaded nano-barium titanate (SBT) was prepared by citric acid complex sol-gel method and then its structure and adsorption capability to zinc ion in water were investigated. The results showed that the nano-barium titanate prepared sol-gel method could be steadily loaded on the surface of silica gel G to produce a cocoon particle adsorption material. This adsorbent had strong absorption capacity to zinc ion in water at pH 4-8 and the static absorption capacity was up to 43.5 mg/g. Zinc ion adsorbed to the adsorbent could be totally eluted by 0.5 mol/L nitric acid and then determined by flame atomic absorption spectrometry. The detection limit of this method was 0.5 μg/L. The RSD was 2.2 % for six independent adsorptions and determinations of zinc ion with initial concentration of 10 μg/L. The method has been applied to the enrichment and determination of trace zinc ion in water with the recovery of 94.9-105.6 %.